Major bleeding and thromboembolism risks of antithrombotic treatment in patients with incident atrial fibrillation/flutter and a history of cancer - Nienke van Rein; Gordon Chu; Menno V. Huisman; Lars Pedersen; Henrik T. Sørensen; Frederikus A. Klok; Suzanne C. Cannegieter (Research and Practice in Thrombosis and Haemostasis)
Background: Literature shows that atrial fibrillation (AF) patients with a history of cancer have a higher risk of thromboembolism (TE) and major bleeding (MB) compared to patients without. However, cancer type and time between cancer and AF diagnosis is often lacking in such analyses. Objectives: To examine MB and TE rates of AF patients with a prior cancer diagnosis, stratified by cancer type and interval between cancer and AF diagnosis. Methods: This Danish population-based cohort study included all patients aged ≥50 years with incident AF between January 1, 1995, and December 31, 2016, and identified those who had cancer before the AF diagnosis. From hospital and drug prescription databases, data on cancer type, time interval between cancer and AF diagnosis (ie, <1, 1-3, or >3 years), outcomes, and antithrombotic exposure were collected. Follow-up started from the AF diagnosis until the occurrence of an outcome or the end of the 2-year follow-up. Incidence rates (IRs) per 100 patient-years and adjusted hazard ratios (aHRs) with corresponding 95% CIs were calculated using Cox regression. Results: We identified 39,178 patients with incident AF and a prior cancer diagnosis. These patients demonstrated higher MB (IR, 3.35 [3.25-3.45] vs 2.23 [2.29-2.35]) and TE rates (IR, 3.21 [3.11-3.31] vs 2.53 [2.50-2.56]) than those without prior cancer. The higher MB risk in AF patients with a prior cancer diagnosis was observed in all examined time intervals, while a higher TE risk was only observed in those with a cancer diagnosis <1 year prior (aHR, 1.27 [1.16-1.40]). Prior respiratory cancer was associated with increased MB (aHR, 1.37 [1.26-1.48]) and TE risks (aHR, 1.26 [1.15-1.38]). Conclusion: A prior cancer diagnosis confers additional MB and, to a lesser extent and in certain conditions, thromboembolic risks in patients with AF. The type and timing of the prior cancer diagnosis determines the degree of risk.